2020
DOI: 10.1186/s12889-020-09361-6
|View full text |Cite
|
Sign up to set email alerts
|

ART use and associated factors among HIV positive caregivers of orphans and vulnerable children in Tanzania

Abstract: Background: Utilization of antiretroviral therapy (ART) is crucial for better health outcomes among people living with the human immunodeficiency virus (PLHIV). Nearly 30% of the 1.6 million PLHIV in Tanzania are not on treatment. Since HIV positive status is the only eligibility criterion for ART use, it is critical to understand the obstacles to ART access and uptake to reach universal coverage of ART among PLHIV. For the caregivers of orphans and vulnerable children (OVC) LHIV and not on ART, attempts to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
(75 reference statements)
2
14
0
Order By: Relevance
“…e project criteria are detailed elsewhere [15]. After the eligible beneficiaries' consent to be enrolled in the program, the needs of the household are identified and case-specific care plans are developed by community workers.…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…e project criteria are detailed elsewhere [15]. After the eligible beneficiaries' consent to be enrolled in the program, the needs of the household are identified and case-specific care plans are developed by community workers.…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…In Tanzania the THIS report showed that 41.5% of male adults 15 years or older had suppressed viral loads compared to 57.2% of their female peers (29). Regarding disability, in a study in Tanzania, care givers with mental or physical disability were 16% less likely to report adhering to HIV treatment (20). None of these studies showed differences between men with and without disability in suppressing their HIV viral loads.…”
Section: Discussionmentioning
confidence: 97%
“…The standard of HIV/AIDS care was also impaired by microeconomic factors [ 88 ]. Financial assistance for the poor, which includes increasing the country’s health insurance coverage, is an important strategy [ 38 ].…”
Section: Discussionmentioning
confidence: 99%